P Pengaruh Pemberian Jus Tomat Terhadap Perubahan Tekanan Darah Sistolik Dan Diastolik Pada Penderita Hipertensi Di Kelurahan Ladang Bambu Kecamatan Medan Tuntungan : Effect of Giving Tomato Juice on Changes in Systolic and Diastolic Blood Pressure in Hypertension Patients in Ladang Bambu Village, Medan Tuntungan District - Sihombing, Reny Juliana; Sirait, Rumita (Journal of Nursing Invention, 2023)
Background: Hypertension is a degenerative disease that is increasingly common in the community. One of the main problems causing the high prevalence of hypertension is the low awareness and knowledge of the community, which has an impact on non-compliance with treatment. Many people think that hypertension is simply overcome by taking headache medication, which is certainly not appropriate. This phenomenon also occurs in Candirejo Village, Biru-biru District.Purpose: The purpose of this study was to examine the effect of tomato juice consumption on changes in systolic and diastolic blood pressure in patients with hypertension.Methods: This study involved 96 respondents aged 30-65 years who suffered from essential hypertension. The study was conducted from October to December 2023. Respondents' blood pressure was measured five minutes before consuming tomato juice, and then measured again at 30, 60, and 90 minutes after consuming tomato juice. The tomatoes used were ordinary fruit tomatoes consumed by the community.Results: The results of statistical analysis showed the effect of tomato juice administration on reducing systolic and diastolic blood pressure. The largest decrease in blood pressure occurred at 30 minutes after consumption of tomato juice.Conclusion: Giving tomato juice can reduce systolic and diastolic blood pressure in people with hypertension, with the biggest decrease occurring 30 minutes after consumption. These results are expected to benefit the community and can be an alternative solution in the treatment of people with hypertension. Keywords: Hypertension, Tomato Juice, Changes in Systolic and Diastolic Blood Pressure